PREOPERATIVE ANXIETY AS A PREDISPOSING FACTOR FOR POST-ANESTHETIC AGITATION FOLLOWING GENERAL ANESTHESIA IN ADULT PATIENTS - Ira Aprilia Utami Pratikno; Ircham Saifudin; Suryanto; Sindu Sintara; Mayang Wulandari (JTH: Journal of Technology and Health, 2026)
Surgical procedures involve invasive interventions performed for diagnostic or therapeutic purposes and may induce various physiological responses. General anesthesia is commonly administered to suppress consciousness and pain during surgery; however, agitation may occur during post-anesthetic recovery and can be associated with psychological conditions such as anxiety before surgery. This study examined the association between preoperative anxiety levels and post-anesthetic agitation in patients receiving general anesthesia. A cross-sectional design was applied to 71 eligible patients recruited through consecutive sampling according to predefined inclusion and exclusion criteria. The association between the two variables was examined using Spearman’s rank correlation. The analysis demonstrated a statistically significant positive relationship between preoperative anxiety and post-anesthetic agitation (ρ = 0.779, p = 0.001). Thus, higher levels of anxiety before surgery were associated with greater post-anesthetic agitation following general anesthesia. These findings highlight the potential importance of identifying and appropriately managing preoperative anxiety as part of perioperative care for patients undergoing general anesthesia.